x-(-4x+2)=3

Simple and best practice solution for x-(-4x+2)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(-4x+2)=3 equation:


Simplifying
x + -1(-4x + 2) = 3

Reorder the terms:
x + -1(2 + -4x) = 3
x + (2 * -1 + -4x * -1) = 3
x + (-2 + 4x) = 3

Reorder the terms:
-2 + x + 4x = 3

Combine like terms: x + 4x = 5x
-2 + 5x = 3

Solving
-2 + 5x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 5x = 3 + 2

Combine like terms: -2 + 2 = 0
0 + 5x = 3 + 2
5x = 3 + 2

Combine like terms: 3 + 2 = 5
5x = 5

Divide each side by '5'.
x = 1

Simplifying
x = 1

See similar equations:

| 6(3x-1)=2x+9-4x | | -5(2x-4)=-20x-4 | | -(4x-13)+9x+12= | | 4+3x=-5x+20 | | -4y+5=11 | | 2(w+6)=8 | | y=(-2)(28/5)+19 | | 6a^3+36a^2+48=0 | | 196a^2-168a-108= | | -36=6x-2x | | 14+5x=-3(-x+3)-11 | | 130(2x+10)=180 | | d-1=3 | | 10x^2+52x+8=0 | | 18-4n=8-2(1-8n) | | 5x-6y=18 | | 26x+1=25x+5 | | 7=3y-2x | | 18x^2-9xy-14y^2= | | -5x+23=-17 | | 5/7=-5 | | d-4=7 | | x=14x-x^2 | | 3x+8(3.125)=-6 | | 36=2v | | -5(2x-4)=-10x+4 | | -41+x=21 | | -2=2(x-5)-8x | | c-5=5 | | 56x^2+54xy-20y^2= | | 12x+5y=-59 | | 2x^3+4x^2-6x-6=0 |

Equations solver categories